Ambroise Paré IV: The early history of artificial limbs (from robotic to prostheses) - Hernigou, Philippe (Springer-Verlag, 2013)
One of the earliest written references to prosthetics is found in a book published in France in 1579. That year, French surgeon Ambroise Paré (1510–1590) published his complete works, part of which described some of the artificial limbs he fitted on his amputees. As a military surgeon, Paré had removed many a soldier's shattered arm or leg, and he eventually began designing and building artificial limbs to help the men who had been maimed.